217 Sexual Activity of Patients Undergoing Testicular Sperm Extraction. (1st May 2022) - Taniguchi, H; Matsuda, T; Nakaoka, Y; Morimoto, Y
ABSTRACT: Introduction: For couples who wish for a baby, sexual activity (though intercourse) is the only way to conceive naturally. However, the sexual activity of men undergoing testicular sperm extraction (TESE) and factors that influence it among affected couples are not clearly understood. Objective: To examine sexual activity among infertile men undergoing TESE and identify factors that influenced Methods: Married Japanese male patients undergoing TESE were included. Sexual activity during the previous month was surveyed using a questionnaire, and potential predictive factors influencing sexual activity were examined. Results: 226 married men who answered a questionnaire regarding sexual frequency were reviewed retrospectively. Patients' mean age was 35.8 ± 7.5 years (range 23–67) and that of their partners was 32.9 ± 4.5 years (range 23–44). Most couples (n = 193) were in their first marriage, and 33 were re-married. The mean marriage duration was 52.6 ± 42.2 months (range 1–192). Micro-dissection TESE and conventional TESE were performed for 152 and 74 patients, respectively. Overall, the mean sexual activity during the last month was 3.6 ± 2.6 times (range 0–15). Marriage duration was negatively correlated with the frequency of sexual activity (r = −0.23; P < .01). There were no correlations between sexual activity and patients' age, partners' age, marriage type (first marriage/re-married), testicular volume, or serum total testosterone concentration. Regression analysis showed marriage duration (odds ratio [OR] 1.01, 95% confidence interval [CI] 1.003–1.019, P = .009) and testicular volume (OR 0.94, 95% CI 0.88–0.99, P = .033) were significant predictors of low sexual activity (0–1 times/month). There were no significant differences in sexual activity per month between patients treated with micro-TESE and c-TESE; between those in a first marriage and those re-married; and between patients with Klinefelter syndrome and patients who underwent c-TESE. Conclusions: The sexual activity of patients undergoing TESE was almost the same as reported previously. Patients' age, partners' age, testicular volume, and serum total testosterone concentration had no correlations with the reported frequency of sexual activity. Disclosure: Work supported by industry: no.